Smart receiver system of green hybrid antennas. Issue 4 (27th February 2013) - Jamlos, M.F.; Kamarudin, M.R.; Malek, M.F.; Jusoh, M.; Jamlos, M.A.
Abstract A hybrid of multiformities receiver system is proposed in this article.The system is developed through a combination of reconfigurable beam‐steering antenna, reconfigurable beam‐shaping antenna, and data acquisition (DAQ) boards. The combination of beam‐steering antenna with beam‐shaping antenna formed a hybrid four‐layer structure with fabricated element plank of rice husk placed between the beam‐shaping antenna's feed line and beam‐steering antenna's radiating element. This four‐layer hybrid and element plank are held together by 5 mm PCB supports at every edge of the antennas forming a stack configuration. The PIN diode switches of both antennas are connected with DAQs to adaptively control the degree angle and beamwidth of the radiation patterns. The activation of either beam‐steering antenna or beam‐shaping antenna depends on the DAQs' Beam Manager memory and the weakest level of received signal strength. When the transmitted signal is coming from the angle of 0°/360°, 90°, 180°, and 270°, its range and angles' location will automatically be detected by the first DAQ that is connected to the beam‐steering antenna. Meanwhile, the beam‐shaping antennas are activated by the second DAQ, to receive the transmitted signal for a longer range at four different gains: 3.6 dB, 7.2 dB, 9.9 dB, and 14.64 dB. Hence, this hybrid receiver system collectively contributes to the well‐developed eight‐multiformity radiation patterns that can be inter‐changed within only 0.01 ms. Furthermore, signal reliability is paramount since the system could self‐elucidate the mutual coupling effects with the aid of rice husk element plank, which acts as a RF absorber. © 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:800–809, 2013; View this article online at wileyonlinelibrary.com. DOI: 10.1002/mop.27412